Genome-wide analysis of the Brachypodium distachyon (L.) P. Beauv. Hsp90 gene family reveals molecular evolution and expression profiling under drought and salt stresses - Zhang, Ming (PLoS One, 2017)
The structure, evolution, and function of heat shock proteins 90 (Hsp90s) have been investigated in great detail in fungi and animals. However, studies on the Hsp90 genes in plants are generally limited. Brachypodium distachyon (L.) P. Beauv., as a model plant for cereal crops, has become a potential biofuel grass. During its long evolution, the Hsp90 gene family in Brachypodium has developed some strategies to cope with adverse environments. How the Hsp90 gene family in Brachypodium evolved in different plant lineages and what its role is in plant responses to drought and salt stresses remains to be elucidated. We used a set of different bioinformatics tools to identify 94 Hsp90 genes from 10 species representing four plant lineages and classified into three subgroups. Eight BdHsp90 genes were detected from B. distachyon. The number of exon-intron structures differed in each subgroup, and the motif analysis revealed that these genes were relatively conservative in each group. The fragments duplication and tandem duplication, which are the prime powers for functional diversity, generally occurred during the duplication of the whole plant genome. Transcriptional analysis of the BdHsp90 genes under salt and drought stress conditions indicated that the expression of these genes was delayed or increased at different stress time points; The expression was more affected in that of Bradi3g39630, Bradi4g06370, and Bradi1g30130. Our findings suggest the involvement of BdHsp90s in plant abiotic stress response, and further consolidate our views on the stress response mechanism of Hsp90 in general.